Human umbilical cord-derived mesenchymal stem/stromal cells: a promising candidate for the development of advanced therapy medicinal products - Mebarki, Miryam (Stem Cell Res Ther, 2021)
Umbilical cord-derived mesenchymal stem/stromal cells (UC-MSCs) emerge as a perspective for therapeutic use in immune and inflammatory diseases. Indeed, immunomodulatory and anti-inflammatory properties, associated to fewer ethical, availability, and safety issues, position UC-MSCs as a promising active substance to develop medicinal products. Since 2007, UC-MSC-based products are classified as advanced therapy medicinal products (ATMP) according to the European Regulation 1394/2007/EC. This new regulatory status required a total adaptation of stakeholders wishing to develop UC-MSC-based ATMPs. Cell production in tissue and cell banks has been replaced by the manufacturing of a medicine, in authorized establishments, according to the good manufacturing practices (GMP) specific to ATMPs. After a brief description of UC-MSCs, we described in this review their recent use in a large panel of immune and inflammatory pathologies, including early and late phase clinical trials. Despite the use of the same product, we noticed an important heterogeneity in terms of indication, posology and study design. Then, we discussed regulatory and manufacturing challenges for stakeholders, especially in terms of process harmonization and cells characterization. Our aim was to point that despite MSCs use for several decades, the development of an UC-MSC-based ATMP remains at this day a real challenge for both academic institutions and pharmaceutical companies.